Incidencia de riesgos físicos y mecánicos en la salud y seguridad ocupacional de los trabajadores de la Corporación Fortaleza del Valle - Maybe Estefany, Ramírez Rudas (2017)
The investigation was carried out in the canton of Bolívar, Province of Manabí. The objective of the investigation was to evaluate the incidence of physical and mechanical risks in the occupational health and safety of the workers of the Fortaleza del Valle Corporation. For this purpose, a diagnosis was made of the current situation of the company, focused on the revision of the current legislation, the collection of relevant information and determination of the health and safety of workers, all this was achieved through the application of interviews and surveys aimed at staff. After these activities, the physical and mechanical risks of the company were identified, using the matrices proposed by the General Directorate of Labor Relations. The most significant risks found in the Corporation were: physical (noise, temperature and lighting), and mechanics (irregular floor, disorder, unprotected machinery, work at heights, among others). After identifying the risks in each work area, the risk levels were estimated based on the probability of occurrence, severity of the damage and vulnerability; through the procedure established by the Ministry of Labor and Social Affairs; to then give way to the evaluation of the most significant risks. Finally, an Occupational Health and Safety Plan was drafted for the Fortaleza del Valle Corporation, with the purpose of contributing to the progress of work practices carried out within the company.